KAJIAN KESIAPAN DESA BUKIT SEBAGAI DESA WISATA NAWA SATYA DI KABUPATEN KARANGASEM, BALI - Ni Nyoman Sri Kusuma Wardani; I Nyoman Sukamara (Pranatacara Bhumandala: Jurnal Riset Planologi, 2020)
Bukit Village was determined to be a tourism village in Karangasem Regency through Karangasem Regent's Decree No. 562 / HK / 2018. The determination of the tourism village is based on the Karangasem Regency government program to develop spiritual tourism based on the adat village. Bukit village as a new tourism village that is being developed, has a problems such as there is no exact data that explains the potential of the tourism village. From these conditions, the purpose of this study was to examine the readiness of Bukit Village as a Nawa Satya Tourism Village by identifying the potential and readiness of the components of the tourism village consisting of attractions, accessibility, ancillary, marketing and community assistance. This study uses a qualitative approach with evaluative analysis. Data in this research were taken through interviews, observations and documentation. The result of this study indicate that Bukit Village can be categorized as an embryo tourism village. There are potential villages that meet the criteria of a tourism village as the main product, complementary product and potential product in supporting the existence of a tourism village and there are development plans in each components of the tourism village, although not all plans can be realized.